Bioethics As A Tool To Face Bullying In The EBR. - Ruiz Alvarado, José Rogelio (2019)
In any situation that a country faces and represents a social problem, education will always be one of the best weapons of struggle to end it. Regular Basic Education in Peru has changed in recent decades, now it is not only restricted to the acquisition of curricular content, but now it has the so-called transversal axes, which become a background of the educational process including issues With social relevance and oriented to the dissemination of values and principles, always seeking a common good.EBR students face, in addition to their own academic responsibilities and the changes of their stage, a great problem: bullying or better known Bullying, which through its different manifestations directly threaten their human dignity.The internalization that students will carry out of the bioethical principles thanks to the transversality in the educational plans, allows them to identify which situation represents any violation or injury of their human dignity and take the measures to overcome them with the help of the people prepared for it.